(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Cultural historiographies have extensively documented the contributions of Beat Generation in giving effect to the spread of countercultures that eventuated in 1960s. The Beat phenomena incorporated divergent and often conflicting emotions, simultaneously and with equal ease. Therefore in beat literature it is not uncommon to find spiritual ecstasy and erotic sensations expressed concurrently. They advocated guilelessness, exposedness, incertitude, and eccentricity while defying restrictions, suppressions, material considerations and authority. The Beat Generation of Allen Ginsberg, William S. Burroughs, Jack Kerouac and Neal Cassady exercised a major impact upon other contemporary maverick movements. A trend of experimenting with the conventional art forms was ongoing in the America of 1950s, which ranged from Expressionist painting to San Francisco Renaissance and from New York Poets to Black Mountain School. The Beat Generation too was the outcome of that impatience which was aiming to disrupt the accepted artistic notions. Writers of this Generation were disgusted by the high and phony artistic discourses such the one expressed by New Critics and New York intellectuals. The writings of this Generation were reacting to various socio-political developments like paranoia of cold war, neo-colonialism and rising trends of capitalism. The object of this paper is to foreground socio-cultural factors that conditioned the writing of Beat Generation.